Validated HPTLC Method for Quantification of Luteolin and Apigenin in Premna mucronata Roxb., Verbenaceae - Nayan G. Patel; Kalpana G. Patel; Kirti V. Patel; Tejal R. Gandhi (Advances in Pharmacological Sciences)
A simple, rapid, and precise high-performance thin-layer chromatographic method was developed for quantitative estimation of luteolin and apigenin in Premna mucronata Roxb., family Verbenaceae. Separation was performed on silica gel 60 F254 HPTLC plates using toluene : ethyl acetate : formic acid (6 : 4 : 0.3) as mobile phase for elution of markers from extract. The determination was carried out in fluorescence mode using densitometric absorbance-reflection mode at 366 nm for both luteolin and apigenin. The methanolic extract of Premna mucronata was found to contain 10.2 mg/g % luteolin and 0.165 mg/g % of apigenin. The method was validated in terms of linearity, LOD and LOQ, accuracy, precision, and specificity. The calibration curve was found to be linear between 200 and 1000 ng/band for luteolin and 50 and 250 ng/band for apigenin. For luteolin and apigenin, the limit of detection was found to be 42.6 ng/band and 7.97 ng/band while the limit of quantitation was found to be 129.08 ng/band and 24.155 ng/band, respectively. This developed validated method is capable of quantifying and resolving luteolin and apigenin and can be applicable for routine analysis of extract and plant as a whole.